2016
DOI: 10.1002/etc.3548
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics and time-variable toxicity of cadmium in Oppia nitens Koch (Acari: Oribatida)

Abstract: The soil-living mite Oppia nitens Koch has recently been proposed as a promising test species for the ecotoxicological risk assessment of contaminated boreal soils. Adding oribatid mites to the assemblage of test species for soil is highly desirable given the enormous diversity and ecological significance of these microarthropods. The authors aimed at revealing how toxicity, lethal body concentration, and bioaccumulation of cadmium (Cd) changed over a period of 7 wk when mites were exposed to Cd-spiked natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…3). For the unexposed controls, the background concentration of Cd in Lufa 2.2 soils was low (0.6 ± 0.2 mg Cd kg -1 dw, Figure 1) and consistent with previous reports for the same soil [e.g., 0.38 mg Cd kg -1 dw, (Keshavarz Jamshidian et al, 2017)]. In the control soil, less than 10 % of the total background Cd concentration was water and acid extractable, indicating that the background Cd in the control soil was not mobile.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…3). For the unexposed controls, the background concentration of Cd in Lufa 2.2 soils was low (0.6 ± 0.2 mg Cd kg -1 dw, Figure 1) and consistent with previous reports for the same soil [e.g., 0.38 mg Cd kg -1 dw, (Keshavarz Jamshidian et al, 2017)]. In the control soil, less than 10 % of the total background Cd concentration was water and acid extractable, indicating that the background Cd in the control soil was not mobile.…”
Section: Discussionsupporting
confidence: 91%
“…Cadmium is a non-essential metal and known to bioaccumulate in earthworms (Hopkin, 1989). The background concentrations of Cd in soil are usually around 1 mg kg -1 dry weight (dw) or less (Keshavarz Jamshidian et al, 2017), but contaminated soils can have tens of mg of Cd (Spurgeon et al, 1994). Dissolved cadmium toxicity is well established in earthworms; with a 28-day lethal concentration (LC50) of 588 mg Cd kg -1 dw in artificial soil (Van Gestel et al, 1991), and 56-day EC50 for impairment of reproduction of 46.3 mg Cd kg -1 dw in artificial soil (Spurgeon et al, 1994).…”
mentioning
confidence: 99%
“…Considering the metals’ effects on survival and reproduction, Cd was the most toxic metal to the mites, having the lowest median lethal concentration (LC50) value, 603 mg/kg, and the lowest reproduction median inhibitory concentration (EC50) value, 137 mg/kg. Keshavarz Jamshidian et al () reported a higher reproduction EC50 value of 345 mg/kg Cd in LUFA 2.2, a natural reference soil. Cadmium has been linked to deleterious effects on the community structure of mites in metal‐contaminated soils (Khalil et al ).…”
Section: O Nitens In Soil Ecotoxicologymentioning
confidence: 98%
“…The toxicokinetics of Cd to O. nitens after a 7-wk exposure in LUFA 2.2 soil showed O. nitens to be a steady accumulator of Cd, with reduced elimination or depuration. Lethal body estimates ranged from 44 to 91 µg Cd/g dry body weight (Keshavarz Jamshidian et al 2017). Table 3 presents the response of O. nitens to contaminants in comparison with other soil invertebrate species used in soil ecotoxicity testing.…”
Section: Toxicokinetics Of Contaminants In O Nitensmentioning
confidence: 99%
See 1 more Smart Citation